Current spreading in GaN-based light-emitting diodes - 李强 李虞锋 张敏妍 丁文 云峰 (Chinese physics B, 2016)
We have investigated the factors affecting the current spreading length（CSL） in GaN-based light-emitting diodes（LEDs） by deriving theoretical expressions and performing simulations with APSYS.For mesa-structure LEDs,the effects of both indium tin oxide（ITO） and n-GaN are taken into account for the first time,and a new Q factor is introduced to explain the effects of different current flow paths on the CSL.The calculations and simulations show that the CSL can be enhanced by increasing the thickness of the ITO layer and resistivity of the n-GaN layer,or by reducing the resistivity of the ITO layer and thickness of the n-GaN layer.The results provide theoretical support for calculating the CSL clearly and directly.For vertical-structure LEDs,the effects of resistivity and thickness of the CSL on the internal quantum efficiency（IQE） have been analyzed.The theoretical expression relating current density and the parameters（resistivity and thickness）of the CSL is obtained,and the results are then verified by simulation.The IQE under different current injection conditions is discussed.The effects of CSL resistivity play a key role at high current injection,and there is an optimal thickness for the largest IQE only at a low current injection.